2012
DOI: 10.4314/sajas.v42i4.3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding the seeds of <i>Prosopis laevigata, Acacia schaffneri</i> and <i>Ceratonia siliqua</i> on the performance of broiler chicks

Abstract: The aim of the present study was to assess the nutrient contents and potential feeding value in the diet of broiler chicks of the seed of three tree species, mesquite (Prosopis laevigata), Schaffneri´s wattle (Acacia schaffneri) and the carob tree (Ceratonia siliqua). The dry matter (DM), ash, crude protein (CP), amino acid and fatty acid concentrations of the seeds were determined. Growth performance was measured in terms of weight gain, feed intake and feed conversion ratio. Sixty-four day-old Cobb broiler c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“… Álvarez-Fuentes et al (2012) had recorded a significant decrease in feed intake and weight gain and a height increase in conversion ratio in chicks fed with a diet containing 30% of carob seeds compared to the control. In this respect, Ortiz et al (2004) observed an important reduction (12.7 and 29.5%) of the apparent digestibility coefficients in chicks fed diets containing 6 and 9% of carob seeds in the starter period compared to the control.…”
Section: Resultsmentioning
confidence: 99%
“… Álvarez-Fuentes et al (2012) had recorded a significant decrease in feed intake and weight gain and a height increase in conversion ratio in chicks fed with a diet containing 30% of carob seeds compared to the control. In this respect, Ortiz et al (2004) observed an important reduction (12.7 and 29.5%) of the apparent digestibility coefficients in chicks fed diets containing 6 and 9% of carob seeds in the starter period compared to the control.…”
Section: Resultsmentioning
confidence: 99%
“…A few researchers have broadened the scope of mesquite feedstock inclusion to address animals other than small ruminants. Feed intake, feed conversion ratio, and weight gain were all decreased when P. laevigata seeds were fed in isonitrogenous diets to broiler chicks [ 13 ]. Average daily gain of rabbits was not affected by inclusion of P. africana pulp, though feeding costs and cost of production were decreased with increasing inclusion [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dutta et al [ 7 ] found that leaves of P. cineraria (L.) Druce improved the digestibility coefficients of all measures of nutritive value when supplemented to a rice straw diet in goats, while Bhatta et al [ 8 ] found mixed results of P. cineraria leaf supplementation of lambs and kids. Much of the interest in feeding mesquite species to livestock has revolved around the use of pods [ 9 , 10 , 11 , 12 ] or seeds [ 13 ] as a protein source as mesquite belongs to the Fabaceae family [ 5 ]. Few, though, have investigated the total biomass of mesquite.…”
Section: Introductionmentioning
confidence: 99%
“…These properties might be associated with the presence of various phytochemicals like alkaloids, saponins, tannins, flavonoids, flavanols and total phenolic (Malik et al, 2013 and Garg and Mittal, 2013). Pods from different Prosopis species have been evaluated in the diet of rabbits (Adamu et al, 2013), poultry (Alvarez‐fuentes et al, 2012; Girma et al, 2011) and fish (Bhatt et al, 2011) to promote carcass growth. However, there is no reports of utilization of Khejri pod and seed meal in fish feed.…”
Section: Introductionmentioning
confidence: 99%
“…Pods from different Prosopis species have been evaluated in the diet of rabbits (Adamu et al, 2013), poultry (Alvarez-fuentes et al, 2012;Girma et al, 2011) and fish (Bhatt et al, 2011) to promote carcass growth. However, there is no reports of utilization of Khejri pod and seed meal in fish feed.…”
mentioning
confidence: 99%